Fin & Lady [large type] - Schine, Cathleen (Thorndike Press, 2013)
It's 1964. Eleven-year-old Fin and his glamorous, worldly, older half sister, Lady, have just been orphaned. Lady, whom Fin hasn't seen in six years, is now his legal guardian and his only hope. That means Fin is uprooted from a small dairy farm in rural Connecticut to Greenwich Village, smack in the middle of t